A model-based strategy to investigate the role of microRNA regulation in cancer signalling networks - Nikolov, Svetoslav; Vera, Julio; Schmitz, Ulf; Wolkenhauer, Olaf (Theory in Biosciences, 2011)
In this paper we present and discuss a model-based approach to link miRNA translational control with cell signalling networks. MicroRNAs are small regulatory RNAs that are able to regulate the activity and the stability of specific messenger RNA and have been implicated in tumour progression due to their ability to translationally regulate critical oncogenes and tumour suppressors. In our approach, data on protein-protein interactions and miRNA regulation, obtained from bioinformatics databases, are integrated with quantitative experimental data using mathematical modelling. Predictive computational simulations and qualitative (bifurcation) analyses of those mathematical models are employed to further support the investigation of such multifactorial networks in the context of cancer progression. We illustrate our approach with the C-Myc/E2F signalling network, involved in the progression of several tumour subtypes, including colorectal cancer.
Keywords: Systems biology; Translational regulation; Bioinformatics; miRNA; Cancer networks